Impact of brachial plexus movement during radical radiotherapy for head and neck cancers: the case for a larger planning organ at risk volume margin. Issue 2 (18th June 2020) - Sarwar, Asma; English, Shelly; Papastavrou, Yanni; Thompson, Anna
Abstract: Introduction: Treatment volumes for radical radiotherapy to head and neck cancers commonly extend into the lower neck, the territory of the brachial plexus (BP). There is a risk of radiation-induced brachial plexopathy, a non-reversible late toxicity experienced by a small number of patients. The BP was anatomically divided into superior and inferior divisions and analysed to establish if segmental inter-fractional BP movement should be considered when planning radiotherapy in this high-dose region. Methods: A retrospective single-centre analysis of 15 patients with head and neck cancers treated with radical bilateral neck irradiation was conducted. The extent of BP movement relative to the planning scan was assessed using weekly cone beam computed tomography (CBCT) scans. The BP was contoured on the planning scan and the subsequent six weekly CBCTs; this was used to calculate the Jaccard Conformity Index (JCI) for the left, right, superior and inferior divisions of the BP. Results: The mean (±SD) JCI for right and left superior BP was 44·4±15·5%, whereas the mean (±SD) JCI for right and left inferior BP was 38·3±15·5%. There was a statistically significant difference between superior and inferior JCI, p =0·0002, 95% CI (−9·26 to −2·88). Bilateral superior BP JCI was higher, with better conformity than the corresponding inferior divisions. Conclusions: Inter-fractional BP movement occurs; the greatest movement is seen at the inferior division. This data suggest the need for re-evaluation of current BP margins and consideration of a larger inferior BP planning at risk volume (PRV) margin.